The Determinants Of Competitive Advantage And Performance Among Shipping Agents In Malaysia - Razak Abd, Afifah (2024)
Malaysia Is Known As A Strategic Maritime Country And Being A Catalyst For The Development Of The Shipping Industry For A Long Time. This Research Examines The Determinants Of Competitive Advantage And Performance Among Shipping Agents In Malaysia. This Research Applies Resources Based View Theory. The Population Of This Study Is Shipping Agents Who Perform The Task Of Delivery And Distribution At Ports In Malaysia. The Sample Of This Study Is Shipping Agents Who Are Active And Registered With Malaysian Immigration Department. A Non - Probability Sampling Approach And Purposive Sampling Techniques Was Used To Select The Samples. The Data Were Analyzed Using Statistical Methods And Modeling Structures By Spss Edition 24 And Smart Pls 2.0 Software. This Research Suggests The Novelty By Measuring Government Procedures That Mediates With Competitive Advantage In Improving Performance For This Industry. The Study Found That The Determinants That Supports The Relationship Between Competitive Advantage And Performance Among Shipping Agents Are As The Management Knowledge, Social Networks, And Government Procedures. The Study Concluded That Competitive Advantage And Performance Among Shipping Agents In Malaysia Have A Significant Positive Effect. The Study Recommends The Determinants Of Competitive Advantage In Improving The Shipping Agents Performance.